Prevalence of cysticercus of Taenia saginata in cattle slaughtered - Faraji, Reza; Nazari, Naser; Negahdary, Masoud (International Journal of Research in Medical Sciences, 2017)
Background: Taenia saginata is a parasite infecting cattle. Human and cattle are as definitive hosts and intermediate hosts, respectively. Humans infected by eating raw or undercooked beef containing larval cysts. The aim of this study was to determine the prevalence rate of T. saginata in cattle in the slaughterhouse of Bistoons Kermanshah (Iran) in 2010-2011. Methods: In order to determine the infection in cattle slaughtered, 100,040 carcasses were observed and inspected along 24 months, from January 2010 until December 2011. Organs like heart, masseter muscles, tongue, triceps muscles, diaphragm, thigh, back ribs, kidney and liver were cut and inspected by eye-and-knife method. Results: In 2010, 29 cases (0.06%) from 48171 and in 2011, 20 cases (0.03%) from 51869 of carcasses were infected. According to the result of this study, the most contaminated organs were heart and tongue. Conclusion: Eye-and-knife method was also less sensitive than standard method (the method used in South Africa, Germany and England) for diagnosis of T. saginata in carcasses.